If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(5x + 1) = 45 Reorder the terms: -5(1 + 5x) = 45 (1 * -5 + 5x * -5) = 45 (-5 + -25x) = 45 Solving -5 + -25x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -25x = 45 + 5 Combine like terms: -5 + 5 = 0 0 + -25x = 45 + 5 -25x = 45 + 5 Combine like terms: 45 + 5 = 50 -25x = 50 Divide each side by '-25'. x = -2 Simplifying x = -2
| 8-2(4y+12)=18 | | n-9= | | 3x*x-2=5x | | y=4x^2-9x-9 | | 3.5/.75x | | y=-3-3/5x | | y=-1/2x2-1 | | 1.07x+5=30 | | 1.7x+5=30 | | 7*6+7= | | 3.5x=.74 | | f(-6)=-3-4 | | b/13-3b/=8/13 | | W=4.2-2L/2 | | 3y=-4x+30 | | $10-3/5= | | 378t-9/7t^2 | | q=2.1 | | Y-5=0(X+3) | | X/7=6-(-8) | | 3x+2x+10=5(x+10) | | 10+15*4= | | 5w-w=8 | | 10.47=2(3.14)(6)(m/360) | | 21=v+2v | | x+3=6x-45 | | 25/y=14 | | 14/4=4 | | xy=2y^2-120 | | 2w-4=-2 | | W=-24-(-13) | | 3x+41=12x-103 |